Optimizing the virtual classroom: A case of intensive English course in the Next Normal - Chayaporn Kaoropthai (Universitas Ahmad Dahlan, 2021)
Due to the COVID-19 pandemic, online learning has automatically become a normal practice of the “Next Normal”. Intensive English is a compact three-week course offered to get first-year students ready for university study. Online learning was something new for both students and instructors. A key challenge in online learning was how to make virtual classroom as lively and interactive as possible. The aim of this study was thus to design an instructional program which integrated various technological tools and applications to optimize the virtual classroom. The 63 first-year students from two intact sections of Intensive English were used as participants of the study. A technology acceptance model (TAM) questionnaire (Davis, 1989; Hernandez, 2021) was adapted to assess the effectiveness of the instructional program. The results of the study revealed that all of the participants achieved the overall objective of the course and the target CEFR’s A2 level. They found their online learning experience rewarding. They were satisfied with this online learning experience and were willing to participate in similar online learning in the future. Additionally, recommendations for further research were discussed.